Evaluasi Program Gerakan Furudhul Ainiyah (Gefa) dengan Menggunakan Model Kirkpatrick - Ridho, Ali; Kusaeri, Kusaeri; Nasaruddin, Nasaruddin; Rohman, Fathur (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2020)
This study discusses the Gerakan Furudul Ainiyah (GEFA) which was conducted in Madrasah of East Java. To value its effectiveness, a comprehensive evaluation of the program and the process of program implementation needs to be conducted, and different evaluations need to be approved. There are several models that can be used to measure the effectiveness of the programs and the implementation processes such as the CIPP model, Stake Countenance, and the others. This study offers a program evaluation model that is the Kirkpatrick model that will evaluate in deeply levels, with four levels namely reaction levels, impact program level, learning change level and outcome level. From those various levels, they are equipped with instruments of assessment.